(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
Studies contradict the belief that everyone that has spinal cord injury (SCI) suffers from depression. This study aims to investigate the level of depression in patients with SCI using the Beck Inventory of Depression with the aim of assessing the scale of the problem and providing clinical intervention in the context of rehabilitation. The inventory was applied to 125 SCI inpatients, between 17 and 63 years-old, being treated in a rehabilitation hospital. Of these, 36.8% suffered moderate to severe depression and 35.2% experienced mild to moderate depression. There was no significant difference in terms of the level of depression, the type of lesion and the duration. In addition to depression, a variety of emotional reactions were observed in different patients with similar sequelae. Research should be conducted to investigate the comorbidity of depression with other illnesses and develop instruments to evaluate depression that eliminate items with low discriminative ability between depression and SCI in the Beck inventory.